Implementasi Metode Electre Dalam Penentuan Karyawan Berprestasi (Studi Kasus: PT. MEGARIMAS SENTOSA) - Mesran Mesran; Selpi Anita; Ronda Deli Sianturi (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2018)
One of the important things that an employee must have is not separated from the performance of an employee. For the effectiveness of human resources work in the assessment of the right decision is needed. Therefore, the software is made that can take a decision to recommend employee achievement for PT. Megariamas Sentosa. The software is built on the basis of a decision support system that has the ability to select outstanding employees using the ELECTRE method. This Electre method has criteria that can determine alternative decisions in application in the software. So that decision makers can determine the selection of outstanding employees. The process in this Electre method compares employees with one employee to another and gives out put value of priority intensity in the form of the assessment result / criteria that has been specified by the company to the employee. The result of this process is recommended as an outstanding employee in PT. Megaria Mas Sentosa.